The Utility of Fecal Calprotectin in the Real-World Clinical Care of Patients with Inflammatory Bowel Disease - Esmail Abej; Wael El-Matary; Harminder Singh; Charles N. Bernstein (Canadian Journal of Gastroenterology and Hepatology)
Objectives. To determine the relationship between fecal calprotectin (FCAL) and imaging studies and other biochemical inflammatory markers and the impact of FCAL measurements on decision-making in IBD patient management in usual clinical practice. Methods. 240 persons with IBD were enrolled. The correlation between FCAL values and other markers for disease activity such as serum albumin (alb), hemoglobin (Hg), and C-reactive protein (CRP) and diagnostic imaging or colonoscopy was examined. FCAL ≥ 250 mcg/g of stool was considered a positive result indicating active IBD. Results. 183 stool samples (76.3%) were returned. The return rate in the pediatric and adult cohorts was 91% (n=82) and 67.3% (n=101), respectively (P<0.0001). Positive FCAL was associated with colonoscopy findings of active IBD (P<0.05), low albumin (P<0.05), anemia (P<0.01), and elevated CRP (P<0.01). There was no significant difference for FCAL results by outcomes on small bowel evaluation among the 21 persons with small bowel CD. Most persons (87.5%) with normal FCAL and no change in therapy remained in remission during subsequent 3 months. Conclusions. FCAL is a useful marker of disease activity and a valuable tool in managing persons with IBD in clinical practice. Clinicians have to be cautious in interpreting FCAL results in small bowel CD.